A pilot study to explore the effects of substances on cognition, mood, performance, and experience of daily activities. Issue 1 (March 2018) - Kiepek, Niki; Beagan, Brenda; Harris, Jonathan
Abstract: Purpose: This pilot study was designed to deliberately examine the enhancement effects and experiences of substances used among professionals and students in professional programs. Methods: A mixed methods design was implemented, involving ecological momentary assessment (EMA) and interviews. The analysis presents interpretations about the perceived impact of substance use on the performance and experience of everyday activities. Results: Caffeine, alcohol, antidepressants, pain suppressant, and cannabis were used by the most participant. Participants reported effects of substances that directly or indirectly enhanced performance (e.g., sleep, socialisation), mood (e.g., manage stress, relax), cognition (e.g., energy and clarity of thought), and the general experience of activities (e.g., enjoyment). Less common effects included impaired work, school, or leisure performance, injury, sleep disruption, and pain or discomfort. Reactivity was an unexpected effect, with almost half of the interviewees reporting changes in their thoughts about their substance use, and 30% of interviewees making active changes. Conclusion: This study was novel in population and data collection. Complex perspectives about substance use were offered by recruiting professionals and students outside at-risk populations or addiction-related services. By examining effects of substances, this research offers nuanced understandings of self-reported effects of psychoactive substances on performance, mood, cognition, and quality of experience.